BUILDING COMMUNITY ENGAGEMENT AND PUBLIC SCHOLARSHIP INTO THE UNIVERSITY. Issue 1 (May 2013) - Whiteford, Linda; Strom, Elizabeth; Bennett, Linda A.; Whiteford, Linda M.
<x xml:space="preserve">Abstract</x> This article, as all of the articles included in this volume, focuses on how "community engagement" and "public scholarship" are being used by public universities to reshape their relations with the students attending the university, and with the communities and other partners with whom the university is engaged. Changing the rules of engagement is provocative and potentially problematic for each of the parties involved. For community partners it raises questions of power differentials, for faculty it raises fears of tenure and promotion confusion, for the university it means taking seriously the legitimate concerns of their neighboring communities, but for students it means real‐life, hands‐on experience with the generation of knowledge from nontraditional sources. That is why it is both exciting and is radicalizing what traditionally has been called "research." The two authors (Whiteford and Strom) discuss how they employed their disciplinary tool kits (from practicing anthropology and political science), as well as their experience with and commitment to community engaged research to negotiate the sometimes rocky shoals of reducing academic barriers and moving a community‐based agenda forward.